The relationship between of ACE I/D and the MTHFR C677t polymorphisms in the pathophysiology of type 2 diabetes mellitus in a population of Brazilian obese patients - Pirozzi, Flavio Fontes [UNESP]; Junior, Edis Belini [UNESP]; Okumura, Jessika Viviani [UNESP]; Salvarani, Mariana [UNESP]; Bonini-Domingos, Claudia Regina [UNESP]; Ruiz, Milton Artur [UNESP] (Archives of Endocrinology and Metabolism, 2018)
Objectives: This study aimed to evaluate the frequencies of the angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) and methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphisms in obese patients with and without type 2 diabetes mellitus (T2DM). Subjects and methods: These polymorphisms were analyzed by polymerase chain reaction in 125 patients with obesity, 47 (T2DM) and 78 (Control Group). Results: No significant difference was found on comparing the T2DM and Control Groups in respect to the genotypic frequencies of the polymorphisms - (II: 13.3% vs. 12.0%; ID: 37.8% vs. 37.3; DD: 48.9% vs. 50.7%; CC: 36.2% vs. 39.0%; CT: 46.8% vs. 49.3%; TT: 17.0% vs. 11.7%), and alleles (I: 32.2% vs. 30.7%; D: 67.8% vs. 69.3%; C: 59.6% vs. 63.6%; T: 40.4% vs. 36.4%) and their synergisms in the pathophysiology of T2DM. On analyzing the T2DM Group, there were no significant differences in the presence of complications. In this population of Brazilian obese patients, no correlation was found between the ACE and MTHFR polymorphisms in the development of T2DM. Conclusion: Analyzing only the group with diabetes, there was also no relationship between these polymorphisms and comorbidities.
Keywords: Angiotensin-converting enzyme gene; Methylenetetrahydrofolate reductase gene; Obesity; Polymorphism; Type 2 diabetes mellitus